2018
DOI: 10.1016/j.ijfoodmicro.2017.10.013
|View full text |Cite
|
Sign up to set email alerts
|

High load of hepatitis E viral RNA in pork livers but absence in pork muscle at French slaughterhouses

Abstract: Pork ham muscle can be contaminated with HEV via blood vessels during viremia and represents a possible source of human contamination via the consumption of dried ham. This study evaluated the prevalence of HEV RNA in pork ham muscles and pork livers at slaughterhouses. Serology was determined on the corresponding serum samples. The apparent individual seroprevalence rate in the 49 pig farms studied was 59% [55.5%-61.4%]. None of the 1134 ham muscles tested was positive for the presence of HEV. HEV prevalence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 37 publications
8
35
0
Order By: Relevance
“…This result is also in agreement with reports from a variety of European countries, as the seroprevalence described in farmed pigs ranged from 30 to 98% (Salines et al, 2017). Besides, in swine abattoirs, results are similar as for example a 59% (55.5-61.4%) of HEV seroprevalence was recently found in France (Feurer et al, 2018). Interestingly, in our study, a total of seven animals resulted negative for HEV detection by both ELISA and RT-qPCR tests, which indicates that only a maximum of 15.56% (95% CI: 7.75-28.7) was not previously in contact or infected by HEV.…”
Section: Discussionsupporting
confidence: 92%
“…This result is also in agreement with reports from a variety of European countries, as the seroprevalence described in farmed pigs ranged from 30 to 98% (Salines et al, 2017). Besides, in swine abattoirs, results are similar as for example a 59% (55.5-61.4%) of HEV seroprevalence was recently found in France (Feurer et al, 2018). Interestingly, in our study, a total of seven animals resulted negative for HEV detection by both ELISA and RT-qPCR tests, which indicates that only a maximum of 15.56% (95% CI: 7.75-28.7) was not previously in contact or infected by HEV.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding HEV prevalence, our data were dated (2009) and HEV prevalence is likely to vary over time. However, a more recent study also conducted in France reported similar prevalence figures (59% seroprevalence in Feurer et al (2017) vs 65% in Rose et al (2011)). Aggregating movement data on a yearly basis also appeared to be relevant due to the absence of seasonality in the French pig network Salines et al, 2017b) and provided indicators representing the overall activity of farms over a year.…”
Section: Discussionmentioning
confidence: 58%
“…The seroprevalence in some regions of Belgium was estimated around 15% [9]. Several studies in Europe have found up to 90% HEV-seropositive pigs on farms and HEV RNA was detected in up to 45% of pigs at slaughterhouses [10-13].…”
Section: Introductionmentioning
confidence: 99%